Correlates of hepatitis B awareness and disease-specific knowledge among pregnant women in Northern and Central Uganda: a cross-sectional study - Nankya-Mutyoba, Joan; Aizire, Jim; Makumbi, Fredrick; Atuyambe, Lynn; Ocama, Ponsiano; Kirk, Gregory D. (Hepatology, medicine and policy, 2018)
Countries in sub-Saharan Africa with a high hepatitis B burden also have limited resources to identify underlying drivers of disease among key at-risk populations. To improve prioritization and strengthen prevention of mother to child transmission of HBV, it is imperative to understand disease awareness, knowledge and related factors among pregnant women. Objectives: This study assessed HBV disease awareness, knowledge and related factors among pregnant women in public health facilities in two regions with diverse HBV disease epidemiology. Methods: From October 2016 through December 2017, a random sample of 455 pregnant women attending antenatal clinics were surveyed to assess HBV awareness, knowledge and associated factors. Participants responded to an 18-item questionnaire with themes on HBV awareness, knowledge of disease signs and symptoms, transmission, prevention and misconceptions about the disease. Results were analysed in STATA (version 14.0). Results: Of 455 participants enrolled, about two thirds reported having heard about HBV disease. By region, nearly half (47%) of participants from the central region, compared to only 16% from the north, reported that they had never heard of HBV. Region of residence had a moderating effect on the education- HBV awareness relationship. Only 162/455 (36%) of participants had adequate HBV knowledge. More than half 256/455 (56%) and 242/455 (53%) were not knowledgeable about horizontal and mother to child HBV transmission, respectively. About two thirds 298/455 (66%) and 281/455 (62%) believed HBV was spread via sharing of utensils and mosquito bites respectively. In multiple regression analysis, residing in the north, (PR=1.91(1.53 -2.38), p < 0.001) compared to central region and having a secondary education (PR=1.87(1.37 -2.55), p < 0.001) compared to primary were statistically significantly related to being knowledgeable about HBV. Conclusion: We demonstrated marked regional differences in HBV disease awareness and knowledge in this high HBV prevalence setting. However, most pregnant women displayed unacceptably low HBV knowledge and a significant proportion still hold misconceptions about HBV. Interventions to improve HBV prevention through antenatal education will need to be tailored to existing differences in comprehensive HBV knowledge.
Keywords: Hepatitis B; Awareness; Knowledge; Pregnant Women